(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The article presents two theater workshops offered to the deaf people and developed online through virtual platforms during the year 2020. Two processes dramas are analyzed, highlighting teaching strategies that consider the references of the deaf and the use of the Brazilian Signal Language (Libras). The resources offered by the chosen platforms were integrated into the Process Drama, stimulating the elaboration of a pretext that dialogues with the virtual environment and contributing to the expansion of the scenic game during the development of the processes.